1988
DOI: 10.1093/ajcn/47.4.675
|View full text |Cite
|
Sign up to set email alerts
|

Particle size of wheat, maize, and oat test meals: effects on plasma glucose and insulin responses and on the rate of starch digestion in vitro

Abstract: When normal volunteers ate isocaloric wheat-based meals, their plasma insulin responses (peak concentration and area under curve) increased stepwise: whole grains less than cracked grains less than coarse flour less than fine flour. Insulin responses were also greater with fine maizemeal than with whole or cracked maize grains but were similar with whole groats, rolled oats, and fine oatmeal. The peak-to-nadir swing of plasma glucose was greater with wheat flour than with cracked or whole grains. In vitro star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
4
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(119 citation statements)
references
References 24 publications
6
105
4
4
Order By: Relevance
“…Although the instructions on the packet were followed, a number of subjects did not find the rice pleasant to eat and may have swallowed much of it with little chewing. Read et al (1986) demonstrated that swallowing food without chewing significantly reduced the blood glucose responses, and foods with small particle size have been shown to produce higher glycaemic responses than foods with larger particle size (Heaton et al, 1988;Holt & Brand Miller, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although the instructions on the packet were followed, a number of subjects did not find the rice pleasant to eat and may have swallowed much of it with little chewing. Read et al (1986) demonstrated that swallowing food without chewing significantly reduced the blood glucose responses, and foods with small particle size have been shown to produce higher glycaemic responses than foods with larger particle size (Heaton et al, 1988;Holt & Brand Miller, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…influence the digestibility of starch. Processing that reduces particle size, such as cracking of wheat grains, increases the in vitro digestibility of raw starch (Heaton et al, 1988).…”
Section: Increased Digestibility Of Cooked Starchmentioning
confidence: 99%
“…For example, it reduces the particle size of raw plant items, leading to improved digestibility (Heaton et al, 1988). (However, pounding still leaves starch granules intact;…”
Section: The Impact Of Cooking On Human Evolutionmentioning
confidence: 99%
“…The use of high-speed roller mills to very finely grind cereals removed almost all of the indigestible material and increased the yield and palatability. The starch was thus made much more digestible and the postprandial glycaemic and insulin responses were 2 -3-fold higher compared to coarsely ground flour or whole grain (Brand et al, 1985;Heaton et al, 1988). At about the same time potatoes were introduced into Western diets and they too have been shown to produce high glycaemic and insulin responses (Jenkins et al, 1988).…”
Section: The Evolution Of Dietary Carbohydratementioning
confidence: 99%
“…At the end of the last Ice Age the population was insulin resistant. The introduction of increased quantities of low glycaemic index carbohydrate with the advent of agriculture elicited only a small postprandial glucose and insulin response (Jenkins et al, 1984;Heaton et al, 1988). Thus, although the carbohydrate content of the diet had increased as a result of agriculture, the insulin-producing pancreatic beta cells were not unduly stressed.…”
Section: The Evolution Of Dietary Carbohydratementioning
confidence: 99%